Induction of chromosomal aberrations by zinc phosphide in of illiteracy sperm cells and eggs laboratory rats (Baghdad Science Journal, 2025)
1 - is not affected by illiteracy cells painful eggs after the first and seventh of the various concentrations used but found the effect of 21 and 35 days after treatment2 - repeat chromosomal aberrations illiteracy eggs cells no different distortions occurring sperm cells During Altnavra phase3 - increased chromosomal aberrations increase the dose especially for 21 and 35 days4 - The connective tissue is more sensitive phase of the pesticide from Altnavra phase